Perlindungan Hukum Hak Privasi Warga Negara terhadap Kebocoran Data Pribadi di Indonesia - Tamam, Badrut; Ikrom, Moh Bagas Fadhli Dzil (Constitution Journal, 2024)
This research is library research that is normative jurisprudence. With a statue approach and a conceptual approach (conceptual approach), We conduct the analysis by descriptively examining the pertinent legal documents, specifically the laws pertaining to the safeguarding of Indonesian citizens' personal data. The purpose of this research is to study the privacy rights regulation in Indonesia and to examine the authority of the parties related to the protection of privacy rights in Indonesia, as well as to study legal protection related to privacy protection in the future. The results of this study show that there are three conclusions: first: the legal protection of the right to privacy through repressive law enforcement in cases of data leakage in Indonesia. Second, the jurisdiction in the judicial protection of privacy rights against data leaks has not been implicitly found in existing regulations, so it requires a specific authority. Third: The legal protection related to privacy protection in Indonesia must be conceived and structured effectively by looking at the legal culture of the people through the mechanisms of the legal tradition in Indonesia in accordance with the theory of the existing system. Abstrak Penelitian ini bertujuan untuk mengkaji perlindungan hukum terhadap hak privasi warga negara Indonesia terkait kebocoran data pribadi dan kewenangan pihak yang berkompeten dalam penanggulangan masalah ini. Penelitian ini merupakan jenis penelitian yuridis normatif yang bersifat library research atau kepustakaan, serta pendekatan Undang-Undang (statute approach) dan konseptual (conceptual approach) untuk menganalisis peraturan yang ada terkait perlindungan data pribadi. Hasil penelitian ini menunjukkan tiga kesimpulan utama: pertama, perlindungan hukum terhadap hak privasi lebih mengandalkan penegakan hukum represif atas kasus kebocoran data di Indonesia; kedua, kewenangan dalam perlindungan hak privasi terhadap kebocoran data belum diatur secara eksplisit dalam regulasi yang ada, sehingga diperlukan instansi yang memiliki kewenangan khusus; ketiga, perlindungan hukum terkait hak privasi di Indonesia di masa depan perlu terkonsep dengan lebih terstruktur dan efektif, memperhatikan budaya hukum masyarakat Indonesia melalui mekanisme tradisi hukum sesuai dengan teori sistem yang ada.